Health care practices of slum dweller adolescent girls in Bangladesh: The case of Sylhet city - Hussain, Muhammed Muazzam; Wakkas, Mphammad Ali (Advances in Social Sciences Research Journal, 2019)
The aim of the paper is to know the health care practices of adolescent girls living in the slum areas of Sylhet city, Bangladesh, understand their health and hygiene issues including treatment, pregnancy, menstruation, vaccination, housing, water and sanitation related challenges they face in their daily lives. The study was based on primary sources of data; however the secondary data e.g. official documents, books, journals, policy papers etc. were used to conduct the study. The study followed qualitative research approach and the case study method to generate sufficient primary data. The study reveals that adolescent girls of slum areas face some menstruation related physical health problems e.g. abdominal pain, irregularity in menstruation cycle, excessive bleeding etc. Sometimes the guardian and doctor do not give much importance on it. The study findings show that adolescent girls of slum areas face multiple health care challenges including low level of personal hygiene, carry on treatment cost, lack of appropriate water, housing and sanitation facilities, etc. The study also highlights that family poverty, behavior of doctors, high cost of medicine, illiteracy of guardian etc. are responsible factors for low uptake of health care services. Therefore, the study suggests for coordinated efforts from the government, local government and voluntary agencies to upgrade their service delivery system.